Prevalence and related factors of comorbid suicide attempts and psychotic symptoms in first-episode drug-naïve patients with major depressive disorder - Aqiong Liu; Huimin Yin; Xiaotang Feng; Lunxin Sun; Junjun Liu; Xiangyang Zhang (BMC Psychiatry)
Abstract Background Psychotic symptoms (PS) and suicide attempts (SA) are especially prevalent in individuals with major depressive disorder (MDD) and serve as key indicators of worsening condition and poor prognosis. This study examined the occurrence of comorbid suicide attempts and psychiatric symptoms (SAPS) in MDD patients, along with the factors associated with these conditions. Methods One thousand seven hundred eighteen first-episode drug-naïve (FEDN) MDD patients were involved in this study, and data on their sociodemographic traits, clinical symptom evaluations, and specific biochemical markers were gathered. Patients were categorised into different clinical subgroups based on the presence of SAPS and were analyzed comparatively. Results About 4.4% of patients had both suicide attempts and psychotic symptoms. Compared to those without SAPS, these patients were older, had an earlier disease onset, and showed higher scores on depression (HAMD), anxiety (HAMA), and illness severity (CGI-SI). They also had different thyroid hormone levels. Higher HAMA (OR = 1.643, 95% CI: 1.439–1.878, p < 0.001), CGI-SI (OR = 8.359, 95% CI: 2.651–26.352, p < 0.001), and TSH levels (OR = 2.025, 95% CI: 1.652–2.842, p < 0.001) were strongly linked to SAPS. The AUCs for HAMA, CGI-S, and TSH were above 0.86, and the combined model yielded an AUC of 0.980. Conclusion These findings highlight the importance of evaluating anxiety, illness severity, and thyroid function in identifying high-risk FEDN MDD patients.